(untitled) (Baghdad Science Journal, 2013)
The present study was conducted to determine the pathogenicity of Paecilomyces farinosus as biocontrol agents against Tragoderma granarium (khapra) under laboratory conditions with three concentrations ( 2.8 x 108 , 2.8 x 106 ,2.8 x104 spores/ ml). The laboratory results revealed that fungi showed it’s higher pathogencity to larve stage on 2nd instar and 6th instar , although their capability differs according to the fungi concentrations this fungi caused higher mortality of 2nd larval instar 70% and 60% ,55% when it was used at concentrations 2 .8 x 106 ,2.8 x104 spores/ ml respectively. On the other hand on 6th larval instars 55% , 35% , 30% at concentrations ( 2.8 x 108 , 2.8 x 106 ,2.8 x104 spores/ ml) respectively, and the highest rate of distortions in the adult insects from the 2nd instar treatment than the adult insects from the 6th instar treatment concentration of this fungi.